A new wide-sense non blocking optical switching network - Rahman, Md. Mahmudur; Hossan, Md. Afzal; Rahman, M.M. Hafizur; Horiguchi, Susumu (2007)
In this paper, we present a new wide-sense nonblocking optical switching network. The proposed network combines some building blocks, which is All-To-All Personalized Exchange Multistage Interconnection Network. The architectural details and some other parameters are evaluated and compared with other networks to show the superiority of the proposed network over other networks. To construct the proposed network we require less number of switching elements. In addition, it provides constant first order crosstalk, thus it scales well. The proposed network is a good choice for constructing nonblocking optical switch with less switching element and signal loss.